Creating a Featured Book Display When Most of the Books are E-books - Patricia E. Reese (Issues in Science and Technology Librarianship)
The Discovery Park Library of the University of North Texas designed a physical featured book display which incorporated both print and electronic books. Using "book dummies" as the base, a template was developed which contained a book cover image and a QR code which would lead the patron to the book in the catalog. Students have used the QR codes to find books, and overall, the book display is leading to increased use of selected items [ABSTRACT FROM AUTHOR]